Thesis writing anxiety among Indonesian pre-service teachers of English: A survey study - Kawengian, Grisel Englin; Subekti, Adaninggar Septi (Englisia: Journal of Language, Education, and Humanities, 2023)
For decades, language anxiety has been a popular research topic in the field of language learning and studies suggested that learners' second/foreign (L2) writing anxiety, one of the anxiety constructs, negatively affected learners' L2 writing achievement. This study aimed to investigate the thesis writing anxiety of Indonesian pre-service English teachers working on their theses in the final semesters of their study. The participants of this study were 105 pre-service teacher participants from ten universities across six different provinces in Indonesia. The study employed an online survey as the method of data collection. It found that generally, the participants had a moderate level of thesis writing anxiety. The detailed findings were further elaborated under four categories: “Difficulty in Grammar and Writing Anxiety”, “Negative Feelings when Writing a Thesis in English”, “Positive Feelings when Writing a Thesis in English”, and “Degree of Influence of Advisors and Peers to Writing Anxiety”. Based on the findings, possible contributions, implications, and limitations are suggested alongside suggested directions for future studies.